Theoretical Principles For Forming Competencies Based On Working With Information In Students - Maftunakhan Botirali kizi Botiraliyeva. (Peerian Journals Publishing, 2024)
This article presents some opinions on the theoretical foundations for the formation of basic competencies for working with information among students. The article also describes the concept of the acmeological approach, its emergence and significance in the educational process
Keywords: Acmeological approach; understanding; education; information